Relations between self-esteem, perceived control, possible selves and academic achievement in adolescents - Leontari, Angeliki; Gialamas, Vasilios (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF